Pendekatan Humanis Dalam Tes Pengajaran Bahasa Arab - Yusuf, Muhammad (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2019)
The purpose of this article is to discuss the humanism approach in Arabic teaching tests. This paper relies on bibliographic sources in the form of books and articles (literature study) that are in a scientific journal related to the subject matter. Reading the data of academics' thinking by using a constructive critical approach and meaningful content with content analysis. Based on studies that have been conducted, teaching tests in the humanist approach must be proportional in measuring each domain that exists in students (cognitive, affective, and psychomotor). The form of tests to measure the domain of cognition can be done by presenting objective tests and description tests. As for the affection domain measurement, it can be done by compiling a Likert scale and semantic different. Meanwhile, to measure the psychomotor domain test can be done in the form of task analysis.